Identification of molecular interactions between P-site tRNA and the ribosome essential for translocation - Feinberg, Jason S. (The National Academy of Sciences, 2001)
Translocation of the tRNA–mRNA complex is a fundamental step in the elongation cycle of protein synthesis. Our studies show that the ribosome can translocate a P-site-bound tRNA(Met) with a break in the phosphodiester backbone between positions 56 and 57 in the TΨC-loop. We have used this fragmented P-site-bound tRNA(Met) to identify two 2′-hydroxyl groups at positions 71 and 76 in the 3′-acceptor arm that are essential for translocation. Crystallographic data show that the 2′-hydroxyl group at positions 71 and 76 contacts the backbone of 23S rRNA residues 1892 and 2433–2434, respectively, in the ribosomal E site. These results establish a set of functional interactions between P-site tRNA and 23S rRNA that are essential for translocation.